The usefulness of inaccurate models: Towards an understanding of the emergence of financial risk management - Millo, Yuval; MacKenzie, Donald (Accounting, organizations and society, 2009)
Is the growth of modern financial risk management a result of the accuracy and reliability of risk models? This paper argues that the remarkable success of today’s financial risk management methods should be attributed primarily to their communicative and organizational usefulness and less to the accuracy of the results they produced. This paper traces the intertwined historical paths of financial risk management and financial derivatives markets. Spanning from the late 1960s to the early 1990s, the paper analyses the social, political and organizational factors that underpinned the exponential success of one of today’s leading risk management methodologies, the applications based on the Black–Scholes–Merton options pricing model. Using primary documents and interviews, the paper shows how financial risk management became part of central market practices and gained reputation among the different organisational market participants (trading firms, the options clearinghouse and the securities regulator). Ultimately, the events in the aftermath of the market crash of October 1987 showed that the practical usefulness of financial risk management methods overshadowed the fact that when financial risk management was critically needed the risk model was inaccurate.